1987
DOI: 10.1530/jrf.0.0790289
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of glucose by human embryos

Abstract: Glucose turnover, as measured by CO2 production, lactate accumulation and carbon incorporation from [U-14C]glucose as sole energy substrate, was low on the 2nd day of culture of human embryos resulting from in-vitro fertilization but above that of unfertilized oocytes. In general, all parameters of metabolism increased substantially during the following 2 days of development but the rate of increase in lactate production was greater than that of CO2, especially between Days 3 and 4. Within developing embryos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The observed increases in oxygen consumption, glucose uptake, and lactate production of bovine embryos as they progress toward the blastocyst stages are consistent with previous studies (Thompson et al, 1996; Guerif et al, 2013), and parallel the well-established increase in embryo energy demand as cell numbers increase (Hardy et al, 1989; Overstrom et al, 1992). The mean values of glucose and lactate flux in bovine embryos in the present study are similar to those previously reported for bovine (Thompson et al, 1996) and human embryos (Hardy et al, 1989; Wales et al, 1987). However, observed rates are lower than those reported for equine embryos (Lane et al, 1996) and bovine and human embryos incubated in lactate-free culture media (Guerif et al, 2013; Gott et al, 1990), suggesting variations due to both species and culture media composition.…”
Section: Resultssupporting
confidence: 91%
“…The observed increases in oxygen consumption, glucose uptake, and lactate production of bovine embryos as they progress toward the blastocyst stages are consistent with previous studies (Thompson et al, 1996; Guerif et al, 2013), and parallel the well-established increase in embryo energy demand as cell numbers increase (Hardy et al, 1989; Overstrom et al, 1992). The mean values of glucose and lactate flux in bovine embryos in the present study are similar to those previously reported for bovine (Thompson et al, 1996) and human embryos (Hardy et al, 1989; Wales et al, 1987). However, observed rates are lower than those reported for equine embryos (Lane et al, 1996) and bovine and human embryos incubated in lactate-free culture media (Guerif et al, 2013; Gott et al, 1990), suggesting variations due to both species and culture media composition.…”
Section: Resultssupporting
confidence: 91%
“…Glycolysis is also used in zygotes and preimplantation embryos, suggesting that ESCs rely on the same energy-generating pathway as their precursor cells. 42 , 43 , 44 ESCs can increase mtDNA copy number in a cell-specific manner during differentiation ensuring that specialised cells acquire the appropriate number of mtDNA copies to meet their specific requirements for OXPHOS-derived ATP. 6 Cancer cells have low mtDNA copy number and rely predominantly on aerobic glycolysis instead of OXPHOS, even under normoxic conditions, which also promotes a highly proliferative state.…”
Section: Discussionmentioning
confidence: 99%
“…Hexokinase may be regulated by compartmentalization Leese et al, 1993). Wales et al (1987) suggested the block to glycolysis in human embryos may be similar to that found in mouse embryos. Human embryos contain the full complement of glycolytic enzymes, although intracellular activities are unknown .…”
Section: Direct Studies Of Metabolism Activity Of Biochemical Patmentioning
confidence: 83%